First comes love : a novel - Giffin, Emily (New York : Ballantine Books, 2016)
While Meredith becomes increasingly unsure about the strength of her bond with her seemingly perfect husband and daughter, her once-happily single sister, Josie, frantically dates and considers her options in her desperation to have a baby.
Keywords: Sisters -- Fiction; Life change events -- Fiction; Mate selection -- Fiction; Domestic fiction; Love stories